Augmentation of Bone Tunnel Healing in Anterior Cruciate Ligament Grafts: Application of Calcium Phosphates and Other Materials. (3rd November 2010) - Baxter, F. R.; Bach, J. S.; Detrez, F.; Cantournet, S.; Corté, L.; Cherkaoui, M.; Ku, D. N.
Abstract : Bone tunnel healing is an important consideration after anterior cruciate ligament (ACL) replacement surgery. Recently, a variety of materials have been proposed for improving this healing process, including autologous bone tissue, cells, artificial proteins, and calcium salts. Amongst these materials are calcium phosphates (CaPs), which are known for their biocompatibility and are widely commercially available. As with the majority of the materials investigated, CaPs have been shown to advance the healing of bone tunnel tissue in animal studies. Mechanical testing shows fixation strengths to be improved, particularly by the application of CaP-based cement in the bone tunnel. Significantly, CaP-based cements have been shown to produce improvements comparable to those induced by potentially more complex treatments such as biologics (including fibronectin and chitin) and cultured cells. Further investigation of CaP-based treatment in the bone tunnels during ACL replacement is therefore warranted in order to establish what improvements in healing and resulting clinical benefits may be achieved through its application.